2018
DOI: 10.1002/jcb.28050
|View full text |Cite
|
Sign up to set email alerts
|

Adenosine protects pancreatic beta cells against apoptosis induced by endoplasmic reticulum stress

Abstract: Chronic exposure to high glucose induces endoplasmic reticulum (ER) stress in pancreatic beta cells (PBCs). The previous evidence showed that adenosine modulate PBCs viability and insulin secretion. The aim of this study was to evaluate possible involvement of adenosine in protection of MIN6 β‐cells from Tunicamycin (Tu)‐induced ER stress. MIN6 cells were cotreated with Tu and different concentrations of adenosine. Cell viability, proliferation, and apoptosis were evaluated using 3‐[4,5‐dimethylthiazol‐2‐yl]‐2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
4
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 46 publications
1
4
0
1
Order By: Relevance
“…These results indicated that GCs were the first cell type that undergoes apoptosis at the initial stage of follicular dominance decline. This result is in accordance with the report by Shahrestanaki et al [32]. Results from Western blot verified that CALR, GRP78, and key transcription factors in the pathways of the ER stress (CALR, p-PERK, PERK, ATF4, ASK1, caspase12, and CHOP) were decreased in D580-SWFs after coculture with D280-SYF-GCs.…”
supporting
confidence: 92%
“…These results indicated that GCs were the first cell type that undergoes apoptosis at the initial stage of follicular dominance decline. This result is in accordance with the report by Shahrestanaki et al [32]. Results from Western blot verified that CALR, GRP78, and key transcription factors in the pathways of the ER stress (CALR, p-PERK, PERK, ATF4, ASK1, caspase12, and CHOP) were decreased in D580-SWFs after coculture with D280-SYF-GCs.…”
supporting
confidence: 92%
“…3×10 5 3T3-L1 differentiated cells were pretreated with klotho (800 pM, 1 h) and then treated with insulin (20 nM insulin for 30 min). Then, as previously described (23), cells were harvested and lysed in ice-cold radio immunoprecipitation assay buffer, 0.5 mM phenylmethylsulfonyl fluoride, phosphatase inhibitor, and 0.5% protease mixture, as previously described (24). Total protein harvested by centrifuging of each sample at 10,000 g for 10 min at 4 °C.…”
Section: Methodsmentioning
confidence: 99%
“…Intracellular calcium oscillations were measured according to the previously published protocol (19). 5000 Cells/well were seeded in the specific florescence clear bottom 384 well plate (PerkinElmer company, Cat: 6007460), overnight.…”
Section: Methodsmentioning
confidence: 99%